Analysis of natural language steganography - Mansor, Shaifizat; Din, Roshidi; Samsudin, Azman (CSC Journal, 2009)
The technology of information hiding through an open network has developed rapidly in recent years. One of the reasons why we need tools to hide message,is to keep secret message concealed from unauthorized party.Steganography is one of the techniques in sending secret message.In this paper, several software metrics were used to analyze the common criteria in steganographic tools and measure the complexity of the tools in hiding message.Several criterias have been chosen: Percent Lines with Comments (PLwC); Average Statements per Function (ASpF) and Average Block Depth (ABD) to measure the tools complexity.The analysis process has been implemented using a single Linux platform.